The Portrait of a Lady - James, Henry, 1843-1916 (London Penguin Books, 1997)
The Portrait of a Lady tells the compelling and ultimately tragic tale of a beautiful young American woman's encounter with European sophistication
Keywords: Americans -- Triangles (Interpersonal relations) -- Italy